The Welsh Institute of Performance Science: A decade of integrated knowledge translation in elite sport - Knight, C. J.; Pankow, K.; Shearer, D. A.; Bringer, J. D.; Davies, B. R.; Lewis, O. C.; Woodfine, S. R.; Kilduff, L. P. (Sports Medicine, 2025)
Sport science researchers and practitioners have noted a gap between research and practice for some time. Although several solutions have been proposed, few recommendations have been made for researchers to follow that are based on successful, long-term sport science research programmes aimed at translating research into practice. Therefore, the purpose of this article is to outline a decade of work completed by the Welsh Institute of Performance Science as an institute for sport-based integrated knowledge translation. The aim is to provide a framework for other researchers and institutes to follow when engaging with organisations for long-term research-to-practice partnerships. In addition to outlining the development and functioning of the Welsh Institute of Performance Science to guide others, limitations of the approach used are also presented and considered to facilitate the future development of sport-specific models of knowledge translation, ensuring that the excellent research conducted across the disciplines of sport science effectively impacts the work of practitioners.